The Integration of Digital Technology in Al-Qur'an Hadith Subject: A Study on Instructional Design Creativity at MTsN 2 Kota Kediri - Khoiriyati, Anti; Sufirmansyah, Sufirmansyah (Institut Agama Islam Negeri Kediri, 2024)
This research aims to explore the creativity of Al-Qur'an Hadith subject teachers in integrating digital technology in the classroom. The concept used is a collaborative learning model with varied IT-based learning media innovations. The research approach uses qualitative field research with a case study type. The methods used to collect data in this research were semi-structured interviews, non-participant observation and documentation. The research results show that the Al-Qur'an Hadith subject teacher at MTsN 2 Kediri has very good creativity. The teacher begins the presentation of the material with a lecture as an introduction and giving trigger questions, followed by a Jigsaw model discussion process and an assignment to make a poster as a Project Based Learning application, followed by clarification and confirmation from the teacher with Canva-based presentation slides displayed on the projector and playing learning videos from YouTube via Smart TV. The instructional design for Al-Qur'an Hadith subjects is based on lesson plans according to KI and KD, combining Jigsaw and Project Based Learning methods, and translating a strong belief in innovation.